The Butterfly Style Swimming Learning Model for Children in the 5 Year Old Group - Herudi, Ersa; Oman U. Subandi; Hernawan (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to produce and test a butterfly stroke swimming learning model for age group 5. The research method uses research and development methods adopted from the theory of Borg & Gall. There are ten steps used in this study, namely needs analysis, initial product development, expert evaluation, small group trials, product revisions, large group trials, product revisions, effectiveness tests, revisions, and the final product. The research subjects were WSC Cirebon children aged 5, totaling 15 subjects in small group trials, large group trials of 40 novice athletes and 40 subject effectiveness tests conducted on children aged 5 at the WSC Cirebon club. The data analysis technique used in this study to test the effectiveness of the model is the normality test, homogeneity test and independent sample-test. The results of the research produced a product in the form of learning to swim the butterfly style for the age group 5. For the age group 5, 28 training models had been validated and revised by experts. The implication of this study is that the learning model is feasible and effective for use for 5 year olds in improving butterfly swimming skills.